Carbohydrate storage in meadow plants and its depletion after disturbance: do roots and stem-derived organs differ in their roles? - Janeček, Stěpán; Klimešová, Jitka (Oecologia, 2014)
Storage of carbohydrates in organs protected from disturbance is an important adaptation of plants in disturbed habitats. We carried out a field experiment involving 31 herbaceous plant species in two cultural meadows to find out whether roots or belowground stem-derived organs (stem bases, stem tubers and rhizomes) are the main storage organs, to study how reserves accumulate in individual organs in the long term (growing season) and to ascertain whether meadow abandonment affects the distribution of carbohydrate reserves in plants. We also conducted a 22-day pot experiment with four meadow plant species to determine how removal of roots and aboveground parts affects the use of carbohydrates stored in roots and stem-derived organs in the short term. From the long-term perspective of the field experiment, mowing had a positive effect on the concentration of carbohydrate reserves. From the short-term perspective of the pot experiment, however, the effect on concentration and pools of carbohydrates was negative. In the field experiment, carbohydrate concentrations before winter were generally higher than in mid-season, and more often higher in roots than in stem-derived organs. Roots and stem-derived organs of plants in the pot experiment were depleted similarly after both types of disturbance. Our results indicate a need for including both types of belowground plant organs in future studies of the carbon economy of plants from disturbed habitats.
Keywords: Carbon; kořeny rostlin; Seasons; sacharidy; rostliny; Carbohydrates; ekosystém; Plant Roots; Ecosystem; roční období; lipnicovité; Czech Republic; uhlík; Plant Stems; Plants; Poaceae; stonky rostlin; Česká republika